Near-Field Virtual Bandwidth Synthetic Aperture Radar Processing for Humanitarian Landmine Detection - Wirth, Sebastian; Morrow, Ivor L.; Andre, Daniel; Finnis, Mark V. (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.This research presents the first experimental demonstration of the Near-Field Virtual Bandwidth SAR (NFVB-SAR) imaging technique. NFVB-SAR is a newly developed sub-surface imaging technique which in contrast to traditional imaging techniques promises subsurface imaging of soils at ultra-high, centimetre-scale resolution using narrow bandwidth. We specifically exploit the differential interferometric SAR phase history of an electromagnetic wave within a drying soil volume to generate high resolution sub-surface mapping from the returned wave through the soil volume. Experiments were conducted at the Cranfield University Antennas and Ground Based SAR (AGBSAR) laboratory using a near-field full polarimetric data acquisition ground penetrating radar. Measurements were taken over a sandy soil containing a buried landmine while the moisture level was varied. - firstly during controlled water addition and then during an extended natural drying out period. As the sand volume dries, the real radar frequency is sequentially transported across a virtual bandwidth of virtual frequencies. The preliminary results demonstrate that even a moderate soil moisture change (SMC) can produce large virtual bandwidths; for e.g. an SMC change of 10% can provide 6cm vertical resolution at X-band. We acknowledge the financial support of the Sir Bobby Charlton Charity "Find A Better Way",10.17862/cranfield.rd.5585245.v1.
Keywords: Horn antenna'; 'Ground-penetrating-radar'; 'SAR imaging'; 'DSDS17'; 'DSDS17 poster'; 'Photogrammetry and Remote Sensing'; 'Antennas and Propagation'